Sosialisasi Penentuan Alternatif Solusi untuk Peningkatan Mutu Pembelajaran Bagi Guru SD di Kabupaten Lombok Utara - Burhanuddin, Burhanuddin; Mahsun; Aswandikari; Sukri; Irma Setiawan; Syaiful Musaddat; syarifuddin (Indonesian Journal of Education and Community Services, 2024)
This community service (abdimas) activity aims to introduce ways to find problems and alternative learning solutions in an appropriate and innovative manner that is in accordance with the empirical learning problems faced by elementary school (SD) teachers in North Lombok Regency (KLU). This is based on the fact that the majority of teachers who take part in the Teacher Professional Education Program (PPG) at Mataram University (Unram) have not been able to find real learning problems. In fact, these teachers have not been able to differentiate the type of problem that arises, whether it is part of the task that must be solved or the task of another party. Methodologically, each stage of the activity carried out to overcome this problem is coordination, communication, presentation and discussion. The results of activities with 30 KLU elementary school teachers as participants in the socialization show what was implied. In relation to this, the Abdimas Team put forward a learning problem discovery strategy carried out in stages: reflection, determining the type of problem, and problem analysis. The strategy for determining alternative solutions has stages: reflecting on causal factors, asking colleagues, asking educational experts, and searching the literature. Each stage can be carried out in stages and in stages that are systemic in nature.